PENGEMBANGAN KURIKULUM BERBASIS PEMBIASAAN DALAM MEMBENTUK KARAKTER RELIGIUS DI SDQT NURUL ISLAM KARAWANG TIMUR - Siti Khulasoh; Agus Susilo Saefullah; Abd Rachman Mildan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of a curriculum based on the habituation of worship in shaping the religious character of students at SD Qur’an Terpadu Nurul Islam Karawang Timur. This research employed a qualitative approach using a case study method. The research subjects consisted of three teachers who were directly involved in implementing religious habituation programs at the school. Data were collected through interviews, observations, and documentation. Data analysis was conducted interactively through the stages of data reduction, data display, and conclusion drawing. The results show that the curriculum development at SD Qur’an Terpadu Nurul Islam does not only focus on academic achievement but also emphasizes the formation of students’ religious character through various worship habituation activities such as congregational dhuha prayer, tahsin and tahfidz Al-Qur’an programs, and congregational dhuhr prayer. In addition, the formation of religious character is strengthened through several supporting programs such as the Ramadan Islamic boarding program, parenting programs for parents, NURI Peduli social activities, and teacher competency development. The implementation of these activities indicates that worship habituation has become part of a character education strategy integrated into the school curriculum and culture.